Pengaruh Jenis Mikroorganisme dan Lama Fermentasi Terhadap Protein Residu Produk Fermentasi Hasil Samping Udang - Yudha Aditya Mahendra; Harun Al Rasyid; Subeki User (Balitbangda Provinsi Lampung, 2016)
Shrimp byproduct is theprocessing shrimp result that still can be used by improving its content through the fermentation process using microorganism. The purpose of this research is to determine the influence of microorganism types and fermentation time using to protein residue of shrimp byproduct fermentation. The research was arranged in factorials in the design random and completed with 2 factors and 3 repetitions.The first factor is types of microorganism, that are Aspergillus niger (M1), Rhizopus oryzae (M2), and Lasiodiplodia theobromae (M3). The second factor is the times of fermentation, that are 0 hours (L0), 24 hours (L1), 48 hours (L2), and 72 hours (L3). Similarities of the data were analyzed and analyzed further by using comparison test and orthogonal polynomials at the level 1% and 5%. The result of research shows that microorganism types and fermentation time have very real impact on protein residue and total yield. Each mold has a tendency in quadratic on total yield and protein residue. But R. oryzae did not have real impact on total yield. The best value of protein residue is A. niger at 4,00% with 35,63 hours of fermentation and the best value of total yield is L. theobromae at 65,92% with 27,70 hours of fermentation.